2020
DOI: 10.1093/brain/awaa209
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants and functional pathways associated with resilience to Alzheimer’s disease

Abstract: Approximately 30% of older adults exhibit the neuropathological features of Alzheimer’s disease without signs of cognitive impairment. Yet, little is known about the genetic factors that allow these potentially resilient individuals to remain cognitively unimpaired in the face of substantial neuropathology. We performed a large, genome-wide association study (GWAS) of two previously validated metrics of cognitive resilience quantified using a latent variable modelling approach and representing better-than-pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 62 publications
8
80
0
Order By: Relevance
“…It is possible, therefore, that sTNFR2 and TNFRSF1B SNPs play a modulating role in regard to clinical outcomes in AD, rather than serving as an AD risk gene that have been the focus of prior genome-wide association studies in AD. This is consistent with prior reports of gene variants related to resilience in AD which suggest that genetic architecture of resilience appears to be distinct from that of clinical AD (Dumitrescu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible, therefore, that sTNFR2 and TNFRSF1B SNPs play a modulating role in regard to clinical outcomes in AD, rather than serving as an AD risk gene that have been the focus of prior genome-wide association studies in AD. This is consistent with prior reports of gene variants related to resilience in AD which suggest that genetic architecture of resilience appears to be distinct from that of clinical AD (Dumitrescu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…In examining published results from the largest available AD case–control GWAS [ 36 ], we cannot find evidence supporting an association of rs12056505 with lower risk of clinically diagnosed probable AD dementia ( p = 0.90, β = 0.997). Clinical diagnosis of AD dementia is by no means a proxy for resilience to AD pathology, and our data more broadly mirrors conclusions from a recent study on resilience in suggesting that the genetic architectures underlying these outcomes are likely to be meaningfully different [ 16 ]. Nevertheless, the lack of clear protective relationship of rs12056505 on clinical AD dementia diagnosis in published data is a limitation.…”
Section: Discussionsupporting
confidence: 78%
“…Although TOMM40 rs2075650 displayed nominal association within a basic model not accounting for APOE ɛ4 ( p = 0.001, β = -0.14), this association was attenuated in the GWAS which included APOE ɛ4 as a covariate ( p = 0.07, β = -0.11). Replication signal was not identified for SNPs reported in prior work to have associations with resilience proxy measures, including RAB10 (RAS oncogene family Rab10) rs142787485 ( p = 0.50, β = 0.03) [ 53 ], BDNF rs6265 ( p = 0.59, β = 0.02) [ 19 ], KL rs9536314 ( p = 0.44, β = 0.03) [ 6 ], and ATP8B1 (ATPase phospholipid transporting 8B1) rs2571244 ( p = 0.28, β = 0.05) [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in many other chronic diseases, AD risk can be influenced by multiple factors, such as age, gender, family history, brain injury, environment, and lifestyle. Notably, results from postmortem autopsy showed that about 30% of cognitively normal people present various signs of AD pathology in the brain ( Arenaza-Urquijo and Vemuri, 2018 ; Dumitrescu et al, 2020 ), raising the question of why some people have AD-like pathology but remain cognitively intact. Individual differences in overcoming adverse factors and thus maintaining a better performance can be a reason.…”
Section: Glycolysis In Admentioning
confidence: 99%